Extragastroesophageal Malignancy-Associated Secondary Achalasia: A Rare Association of Pancreatic Cancer Rendering Alarm Manifestation - Kim, Hong Min; Chu, Ji Min; Kim, Won Hee; Hong, Sung Pyo; Hahm, Ki Baik; Ko, Kwang Hyun (Clinical endoscopy, 2015)
Secondary achalasia or pseudoachalasia is a rare esophageal motor abnormality, which mimics primary achalasia; it is not easily distinguishable from idiopathic achalasia by manometry, radiological examination, or endoscopy. Although the majority of reported pseudoachalasia cases are associated with neoplasms at or near the esophagogastric (EG) junction, other neoplastic processes or even chronic illnesses such as rheumatoid arthritis can lead to the development of pseudoachalasia, for example, mediastinal masses, gastrointestinal (GI) tumors of the liver and biliary tract, and non-GI malignancies. Therefore, even if a patient presents with the typical findings of achalasia, we should be alert to the possibility of other GI malignancies besides EG tumors. For instance, pancreatic cancer was found in the case reported here; only four such cases have been reported in the literature. A 47-year-old man was admitted to our center with a 3-month history of dysphagia. His endoscopic and esophageal manometric findings were compatible with primary achalasia. However, unresponsiveness to diverse conventional achalasia treatments led us to suspect secondary achalasia. An active search led to a diagnosis of pancreatic mucinous cystadenocarcinoma invading the gastric fundus and EG junction. This rare case of pseudoachalasia caused by pancreatic carcinoma emphasizes the need for suspecting GI malignancies other than EG tumors in patients refractory to conventional achalasia treatment.